Composição florística e flutuação espacial e temporal do fitoplâncton do lago tupé (Amazonas, Brasil) - Leão, Bruno Machado (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
The phytoplankton of Tupé Lake, a humic lake in the Central Amazon, was studied regarding its floristic composition and the ecological seasonal dynamics of this community, monthly (July/06 to July/07), in 4 stations in the lake and one in Negro River. Also, a study regarding the diel variation of the community in 2 periods of the hydrological cycle, high waters and low waters (June and November/06) were performed. Water temperature, electrical conductivity, dissolved oxygen and its saturation and total/fractionated nutrients were analyzed. Phytoplankton sampling was carried out using a Van Dorn water bottle and analyzed in inverted microscope, to obtain data on the biovolume, abundance, species richness, diversity and equitability of the community. Also, qualitative samples were taken with plankton nets with 20 µm mesh size and were analyzed with a standard optical microscope, and only the Chrysophyceae with silica scales were analyzed with an scanning electron microscope. The functional groups of the species were determined. The phytoplankton community of Tupé lake consists mainly of species adapted to the dystrophic and meromythic conditions of the lake, being capable of mixotrophy and vertical migration from the illuminated epilimnion to the nutrient-enriched hipolimnion during the periods of high waters, when the water column is deeper, and with the presence of autotrophic species exclusively during the low water period, when the lake had lower hydrometric values, higher nutrients concentrations and penetration of light until closer of the hipolimnion. In the seasonal study a total of 94 taxa were observed, mostly of Chrysophyceae (35 species), followed by Chlorophyceae (17) and Bacillariophyceae (10), with the Chrysophyceae being dominant in the entire study. Gonyostomum semen (Raphidophyceae) had the higher biovolume and dominated in the high water periods samples, which is mainly due to it being mixothropic and its ability to migrate vertically. During the low water period, Dinophyceae and Charophyceae were the classes with predominant biovolume. In the diel vertical migration study, patterns of vertical migration were observed, where higher abundances and volume were registered at the surface in the afternoon, while the species migrated to the bottom at night, resurfacing in the morning. Vertical migration to even deeper layers was observed during the high water period. During the low water period, higher values of biovolume and total abundance were observed as well as autotrophic species which were favored by the high nutrient concentrations and penetration of light closer to the hipolimnion. The most important species, regarding biovolume and abundance, were Gonyostomum semen, Gymnodinium sp2, Pleurotaenium tenuissimum, Cryptomonas brasiliensis, Chomulina cf. minima, C. cf. mikroplankton and C. cf. elegans. It was also verified that the dystrophic profile of the Tupé Lake and the fluctuation of its hydrological level caused by the floodpulse of Negro River regulated the intensity of light penetration, nutrients availability and the distance between epilimnion and hipolimnion, determining the composition and ecology of the phytoplankton community.
Keywords: Dinâmica do Fitoplâncton; Composição florística; Lago húmico; Fitoflagelado; Pulso de inundação